The perceptions and experiences of social representation in the Free State schools: an education management perspective - Bowes, John Hamilton (University of the Free State, 2009)
This thesis examined the discourse of the perceptions and experiences school leaders have on cultural representativity in a changing environment and how such situations should be managed. The ideology behind social representation was justified with the notion that it has the task to level the playing field, so that all South Africans can share democracy, liberty and equality. In South Africa social representation is implemented as a permanent measure to achieve a truly representative society across all spheres in South Africa, which forces diverse groups of society to conform to the goal of a homogeneous society. This affects all cultures and social classes in society and consequently also the school principal in all aspects of school management. The study drew on a comprehensive literature study exploring the philosophical foundations, the principles that underpin social representation, racial, cultural and gender divides, as well as its impact on organisations and suggestions on how to manage diversity in the school. The data that emerged from the literature review was used as point of departure for the empirical investigations. In this investigation a mixed-method approach was followed, using interviews with eight school leaders in the Free State Province and a researcher developed questionnaire that was distributed to 280 school leaders at schools with diverse cultures situated in urban as well as rural communities in the Free State Province. The above investigations revealed how social representation is experienced and perceived, the problems encountered during implementation, what school leaders regard as basic elements to ensure effectively run diverse schools, as well as the training that they would like to undergo in order to become more efficient in running a socially represented school in the present South African context. The researcher came to the conclusion that, in spite of heightened racial sensitivity, school leaders have rather positive feelings about social representation and that the school and the community benefit from it. The study is concluded by a synthesis of the findings resulting in guidelines for the effective management of socially diverse schools. It was finally envisaged that this study will serve as a starting point for training and for the further dissemination of the research findings to the benefit of school management and staff performance in South Africa.

Hierdie studie ondersoek die diskoers rondom die persepsies en ervarings van skoolleiers op die gebied van kulturele verteenwoordiging in ŉ veranderende omgewing en hoe hierdie veranderinge bestuur behoort te word. Die ideologie van sosiale verteenwoordiging word geregverdig met die opvatting dat dit ten doel het om die speelveld gelyk te maak sodat alle Suid-Afrikaners kan deel hê in die beginsels van demokrasie, vryheid en gelykheid. Sosiale verteenwoordiging word as ŉ permanente maatreël in Suid-Afrika geïmplementeer ten einde ŉ waarlik verteenwoordigende gemeenskap oor alle sfere heen in Suid-Afrika tot stand te bring, wat diverse groepe in die gemeenskap dwing om te voldoen aan die doelwit van ŉ homogene samelewing. Dit raak alle kulture en sosiale klasse in die samelewing en gevolglik ook die skoolhoof in alle aspekte van skoolbestuur. Hierdie studie het met behulp van ŉ omvattende literatuurstudie die volgende aspekte ondersoek: die filosofiese onderbou en die beginsels wat ten grondslag van sosiale verteenwoordiging lê, die bestaande kloof tussen rasgroepe, kultuur en geslag en die impak wat bogenoemde aspekte op organisasies uitoefen, asook voorstelle oor hoe om diversiteit in die skool te bestuur. Die data wat uit die literatuuroorsig voortgespruit het, is as uitgangspunt vir die empiriese ondersoek gebruik. ŉ Gemengde-metode-benadering is in hierdie ondersoek gevolg deur gebruik te maak van onderhoude met agt skoolleiers in die Vrystaatprovinsie en ŉ navorser-ontwikkelde vraelys wat onder 280 skoolleiers in skole met diverse kulture versprei is. Die betrokke skole is in stedelike sowel as landelike gemeenskappe in die Vrystaatprovinsie geleë. Bogenoemde ondersoeke het aangetoon hoe kulturele verteenwoordiging ervaar en waargeneem word, die probleme wat tydens implementering ondervind word, die basiese elemente hoe om diverse skole doeltreffend te bestuur volgens die mening van skoolleiers, asook die opleiding wat skoolleiers sal wil ondergaan ten einde kultureel-verteenwoordigende skole in die huidige Suid-Afrikaanse konteks meer effektief te bestuur. Die navorser het tot die gevolgtrekking gekom dat, ten spyte van ŉ verhoogde sensitiwiteit ten opsigte van rasgroepe, skoolleiers redelik positiewe gevoelens rondom kulturele verteenwoordiging ervaar en dat die skool en gemeenskap daarby baat vind. Die studie word afgesluit met ŉ sintese van die bevindings, wat uitloop op riglyne vir die effektiewe bestuur van kultureel-diverse skole. Dit word verder in die vooruitsig gestel dat hierdie studie as uitgangspunt vir opleiding en die verdere verspreiding van die navorsingsbevinding sal dien, tot voordeel van skoolbestuur en die werkverrigting van personeel by skole in Suid- Afrika.
Thesis (Ph.D. (Education Management))--University of the Free State, 2009
Keywords: School management and organizations -- South Africa; Social representations; Educational leadership -- South Africa; School principals -- South Africa; Affirmative action; Cultural diversity; Democracy; Empowerment needs; Equality; Freedom; Human dignity; Philosophies; School effectiveness; School leaders; Transformation